2015
DOI: 10.5194/hess-19-105-2015
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological hysteresis and its value for assessing process consistency in catchment conceptual models

Abstract: Abstract. While most hydrological models reproduce the general flow dynamics, they frequently fail to adequately mimic system-internal processes. In particular, the relationship between storage and discharge, which often follows annual hysteretic patterns in shallow hard-rock aquifers, is rarely considered in modelling studies. One main reason is that catchment storage is difficult to measure, and another one is that objective functions are usually based on individual variables time series (e.g. the discharge)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 73 publications
3
60
0
Order By: Relevance
“…Interpretations of direct and indirect storages also raise the question of appropriate representation of storage dynamics in conceptual hydrologic models. The Elder Creek interpretation aligns with common perceptual understanding of catchment run‐off generation: Unsaturated and saturated moisture dynamics can be treated separately (e.g., Bardossy & Singh, ; Botter et al, ; Fovet et al, ) due to a distinct hydrologic zonation between the dynamic unsaturated zone and hillslope water tables. Interpretation of discharge generation and direct/indirect storage dynamics at Dry Creek, however, presents a more significant challenge for the conceptual hydrologic modeller.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Interpretations of direct and indirect storages also raise the question of appropriate representation of storage dynamics in conceptual hydrologic models. The Elder Creek interpretation aligns with common perceptual understanding of catchment run‐off generation: Unsaturated and saturated moisture dynamics can be treated separately (e.g., Bardossy & Singh, ; Botter et al, ; Fovet et al, ) due to a distinct hydrologic zonation between the dynamic unsaturated zone and hillslope water tables. Interpretation of discharge generation and direct/indirect storage dynamics at Dry Creek, however, presents a more significant challenge for the conceptual hydrologic modeller.…”
Section: Discussionmentioning
confidence: 71%
“…Non‐linear, hysteretic storage–discharge mechanisms are associated with time lags in the transfer of mass or information through a watershed, suggesting that the volume and physical attributes (e.g., saturated vs. unsaturated) of decoupled storage affect catchment transport timescales, hydraulic response to external fluxes, and the sensitivity of evapotranspiration to climate variations (e.g., Nippgen, McGlynn, Emanuel, & Vose, ; Riegger & Tourian, ; Tani, ; Torres et al, ). Conceptual hydrologic models often feature decoupled storage elements (Birkel, Soulsby, & Tetzlaff, ; Botter, Porporato, Rodriguez‐Itubre, & Rinaldo, ; Lehmann, Hinz, McGrath, Tromp van Meerveld, & McDonnell, ), whose process representations are strong determinants of catchment discharge response and the emergent, hysteretic features of modelled storage–discharge relationships (Fovet, Ruiz, Hrachowitz, Faucheux, & Gascuel‐Odoux, ). Thus, estimating the volumes and temporal dynamics of hydraulically decoupled catchment storage could provide important new insights into catchment processes and improve hydrological modelling frameworks.…”
Section: Motivationmentioning
confidence: 99%
“…Refsgaard and Knudsen, 1996;Booij, 2005). Nevertheless, in many cases these models may remain serious over-simplifications of the different combinations of the dominant processes underlying the observed response patterns as argued by, among others, Young (1992), Reichert and Omlin (1997), Perrin et al (2001), Wagener and Gupta (2005), Gupta et al (2012), Zehe et al (2014), Hrachowitz et al (2014) and Fovet et al (2015). In addition, the transferability of these simple models to other (ungauged) basins is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies also illustrated the non-uniqueness of the response of discharge to storage. For instance, Clark et al (2009) illustrated for a mountain watershed in Georgia (USA) that the recession relationships of (dQ/dt) and Q is approximately consistent with a linear reservoir at a hillslope scale and deviation from linearity becomes progressively larger with increasing spatial scale, and Myrabø (1997), Beven (2006), Ewen and Birkinshaw (2007), Spence et al (2010), Martina et al (2011) and Fovet et al (2015 reported hysteresis in discharge-storage relationships. Furthermore, Teuling et al…”
mentioning
confidence: 99%